Average Personal Income Tax Rate and Tax Wedge Progression in OECD Countries - Paturot, Dominique (OECD Publishing, 2013)
The statutory progressivity of the income taxes paid by wage earners, net of the standard cash benefits they receive, depend on the design and interaction of personal income taxes, social security contributions (SSCs) and cash benefits. In order to capture their combined impact, this paper presents statutory tax progressivity indicators for the 34 OECD member countries on the basis of average effective income tax rates and tax wedges which are calculated using the OECD's Taxing Wages framework. The analysis shows a decreasing pattern of tax progressivity across income levels. In some countries, the tax system becomes regressive when the SSC ceiling has been reached. Also, child benefits increase progressivity (especially at low income levels) and their effect is larger than the flattening impact of SSCs, except at top income levels. Reductions in SSCs targeted at low-incomes and dependant spouse allowances increase progressivity in some OECD countries. Income-splitting systems typically have the opposite effect
Keywords: Taxation